The Influence of Hedonic Shopping Value, Shopping Lifestyle, and Gamification on Impulse Buying among Generation Z TikTok Shop Users in Medan City - Ringo, Wenni Siringo; Salqaura, Siti Alhamra; Hasman, Haryaji Catur Putera (International Journal of Education, Information Technology, and Others, 2023)
The phenomenon of rapid development of online shopping and Internet frequency may lead to impulsive buying behaviour due to shopping stimuli and moods. The purpose of this study is to determine: (1) Impact of hedonic shopping value on impulse purchases (2) Impact of shopping lifestyle on impulse purchases (3) Impact of gamification on impulse purchases (4) Impact of hedonic shopping values, shopping lifestyles, and gamification on impulse purchases. The research method used in this study is quantitative with an associative approach. A questionnaire was distributed to 100 respondents of Generation Z who are TikTok shop users in Medan city. The data analysis technique used is multiple linear regression. Here are the research results: (1) Hedonic purchase amount (X1) has a significant positive impact on impulse purchases (Y), as evidenced by t-value 3.199 > t-table 1.660 and significance 0.002, as evidenced by F-value 45.013 > F-table 2.14 and significance < 0.001. 0.1 (2) Shopping Lifestyle (X2) has a positive and significant influence on Impulse Buying, evidenced by t-value 5.091 > t-table 1.660 and a significance of 0.001 < 0.1 (3) Gamification (X3) does not have a significant effect on Impulse Buying variables (Y) but has a positive value. This is evidenced by t-value 1.571 < t-table 1.660 and a significance of 0.120 > 0.1 (4) Hedonic Shopping Value (X1), Shopping Lifestyle (X2), Gamification (X3) together (simultaneously) have a positive and significant effect on the variable Impulse Buying (Y) is evidenced by F-value 45.013 > F-table 2.14 and the significance is 0.001 < 0.1.